IFIP International Federation for Information Processing
DOI: 10.1007/0-387-29773-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Configuring E-Government Services Using Ontologies

Abstract: Abstract:The increasing complexity of e-Government services demands a correspondingly larger effort for management. Today, many system management tasks, such as service verification and re-configuration due to changes in the law, are often performed manually. This can be time consuming and error-prone. The main objective of the OntoGov (IST-2002-507237) project is to overcome the above mentioned problems by developing a semantically-enriched platform that will facilitate the consistent configuration and re-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…As mentioned earlier, OWL is a common language employed for semantic knowledge representation in e-government. In particular, OWL ontologies allow the composition [1], [7], searching, matching, mapping and merging [2], [6] of e-government services and facilitate their integration [1], [2], [5], maintenance [1] and interoperability [3], [4], [6], [7]. Therefore, generating OWL ontology from a government service domain as it is done in this research and in [28] is an important step towards the development of Semantic Web applications as egovernment applications, which have potential to perform semantic inference and reasoning over the OWL ontology and facilitate software components integration and interoperability.…”
Section: Owl Ontology In E-governmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, OWL is a common language employed for semantic knowledge representation in e-government. In particular, OWL ontologies allow the composition [1], [7], searching, matching, mapping and merging [2], [6] of e-government services and facilitate their integration [1], [2], [5], maintenance [1] and interoperability [3], [4], [6], [7]. Therefore, generating OWL ontology from a government service domain as it is done in this research and in [28] is an important step towards the development of Semantic Web applications as egovernment applications, which have potential to perform semantic inference and reasoning over the OWL ontology and facilitate software components integration and interoperability.…”
Section: Owl Ontology In E-governmentmentioning
confidence: 99%
“…The instances of government are department, agency and municipality. Based on equations (1) and (2) Similarly, a manual analysis of each competency question in Table 2 was performed and the main concepts of the development project (DP) domain which are semantically related to the question (see column 2 of Table 6) enumerated. For instance, let's consider the first question (Q1) in Table 2: "What are the current projects being run in a given locality?"…”
Section: Mapping Of Competency Questions With Concepts Of the Formal mentioning
confidence: 99%
See 2 more Smart Citations
“…Although the state-of-the-art software engineering techniques including objectoriented and agile methods provide appropriate solutions to the aforementioned engineering problems of services integration and interoperability in e-government [1], [3], [4], it has been demonstrated that they have certain limitations [3], [4], [5], [6]. Therefore, during the past six years, Semantic Web technologies have emerged as promising solutions to these problems [3], [4], [7], [8], [16].…”
Section: Introductionmentioning
confidence: 99%